Impact of maternal cytomegalovirus seroconversion on newborn and childhood hearing loss. Issue 5 (29th August 2022) - Raynor, Eileen M.; Martin, Hannah L.; Poehlein, Emily; Lee, Hui‐Jie; Lantos, Paul
Abstract: Objectives/hypothesis: The objective of this study is to describe long‐term hearing outcomes in infants born to mothers with a known cytomegalovirus (CMV) positivity who were not tested for congenital CMV . Study type: Clinical research study. Design: Retrospective cohort study. Methods: Retrospective chart review was performed for mothers seropositive to CMV. Mother–infant dyads (130) were identified between January 1, 2013 and January 1, 2017. Outcomes data was collected through June 1, 2020. Demographics, risk factors for hearing loss, evidence of CMV infection, other causes of hearing loss, need for speech therapy services, and results of all hearing tests were collected. Results: All 130 infants were asymptomatic and 5 were tested for congenital CMV. Five were negative for CMV and excluded from analyses. Of the remaining 125, only 1 had low‐viral avidity IgG antibodies. None had IgM antibodies. Four children (3.2%) had hearing loss at last audiogram and one child had delayed onset SNHL due to an enlarged vestibular aqueduct. Speech therapy for communication was required for 33 children (26.4%). Conclusions: Knowledge of maternal perinatal CMV status can allow for education about possible sequelae of cCMV, as well as trigger an alert for testing babies born to mothers with low‐viral avidity IgG during the first trimester, when the risk of vertical transmission is highest. Also, babies born to CMV positive mothers may be more at risk for communication delays necessitating intervention. Studies focusing on the impact of maternal CMV related to childhood communication deficits could elucidate any direct relationships. Abstract : Maternal CMV status may not predict SNHL in untested infants but there seems to be a higher need for speech language therapy services in these children. Possibly knowing the maternal CMV immunologic status during the first trimester can help with education about the need for audiologic and developmental follow up in their children.